The economic effects of Rhyzopertha dominica on rice quality: Objective and subjective measures. (December 2019) - Su, Lianfan; Adam, Brian D.; Arthur, Frank H.; Lusk, Jayson L.; Meullenet, Jean F.
Abstract: Infestations of internal feeders such as Rhyzopertha dominica cause damage to stored grains, including rice. Few studies, though, have measured the economic effects of that damage. In this study, samples of rough long grain rice were infested with R. dominica at several rates (0, 20, and 200 adults/kg). The effects of these infestations on rice quality and quantity were measured objectively using color and milling yield. They were also measured subjectively with a blind taste/sensory consumer taste test and a non-hypothetical auction measuring consumer willingness to pay for the different qualities of rice. The objective quantity and value loss ranged from 2% for lightly-infested rice to 3.5% for heavily-infested rice. For subjective effects, results of the auction suggested that participants on average were willing to pay only a small premium for less infested rice. This test confirmed results of the sensory taste panel, which showed that participants on average detected very little difference among rice samples with alternative levels of infestation. However, when they were given extra information verifying that rice with lower infestation levels was higher quality or that the rice was stored using IPM methods, the potential price increase from reducing R. dominica infestation could range from 0.44/kg. to 0.79/kg., plus a 0.13/kg. premium for using IPM storage methods. However, results suggest that in order to capture that value rice sellers must be able to convey information about quality and storage attributes to consumers in a way that is relevant and trustworthy.